Structure-based virtual screening study for identification of potent insecticides against Anopheles gambiae to combat the malaria - Nawal Helmi (Journal of Vector Borne Diseases, 2024)
Background & objectives: Vector-borne infectious diseases contribute significantly to global mortality, with over 700,000 annual deaths, and malaria alone accounts for more than 400,000 of these fatalities. Anopheles gambiae, a prominent mosquito species, serves as a primary vector for transmitting malaria to humans. To address this issue, researchers have identified the D1-like dopamine receptor (DAR), specifically DOP2, as a promising target for developing new insecticides. Methods: The three-dimensional structure of DOP2 from A. gambiae was unavailable; in-silico approach was used to model and validate DOP2 structure. The Discovery Studio 2021 program was used to identify potential binding sites on DOP2. Virtual screening of 235 anti-parasitic compounds was performed against DOP2 using PyRx 0.8. Results: The screening demonstrated strong binding and interactions with active site residues of DOP2 for five compounds: Diclazuril, Kaempferol, Deracoxib, Clindamycin, and Diaveridine. These compounds exhibited higher binding affinity values compared to the control (Asenapine). In addition, the predicted physiochemical properties for these compounds were within acceptable ranges and there were no violations in drug-likeness properties. Interpretation & conclusion: These compounds show promise as potential new insecticides targeting A. gambiae mosquito by inhibiting the DOP2 protein. However, additional experimental validation is required to optimize their efficacy as DOP2 inhibitors.